AFM investigations of critical interactions in the Bacillus primosome and Cryogenic AFM a new tool for structural biology - Turner, Ian James (2006)
In this thesis for the first AFM has been employed for the high resolution imaging of a protein assembly. The DnaB-DnaG Helicase-Primase interaction in Bacillus is the key reaction that causes the switch from primase mode to polymerisation mode. This assembly was imaged using the AFM to a sub-molecular resolution revealing structural detail of the interaction. It is shown that the binding of the primase causes the structure of the helicase to switch from a hexamer to a trimer of dimers with one primase molecule bound to each dimer; also the existance of sub-populations with one and two primases bound suggests a sequential mode of binding. Recently crystallography data has been published that confirms the structural observations generated by AFM here. This is the first time that AFM and crystallography data have been used concurrently to solve the molecular structure of a protein assembly and it shows the potential application of AFM for sub-molecular resolution imaging of other protein assemblies.